Ester formation in intermittently dried noni fruit (Morinda citrifolia L.). Issue 9 (11th June 2020) - Lin, Chi-Hung; Huang, Tzou-Chi; Chen, Ho-Hsien; Sheu, Shyang-Chwen
Abstract: The formation of aromatic esters in intermittently dried noni fruit by endogenous enzymatic activity was investigated. Gas chromatography mass spectrometry was used to determine the volatile compounds of Morinda citrifolia (noni). Large amounts of free fatty acids, especially hexanoic and octanoic acids, were found in fully matured noni. Significant amounts of esters derived from hexanoic and octanoic acids were detected in dried noni, especially in the product that intermittently dried. We postulate that autolysis occurred during ripening and that ester formation was catalyzed by endogenous lipase under low water activity (0.6 ± 0.1) during the intermittent drying stage. By controlling the water activities of noni fruit, biochemical reactions leading to the transformation of the sharp odor into an aromatic smell in dried noni products were investigated.